PTTG induces EMT through integrin AlphaV Beta3-focal adhesion kinase signaling in lung cancer cells - Shah, Parag P. (2011)
Pituitary tumor transforming gene (PTTG) is a well-studied oncogene for its role in tumorigenesis and serves as a marker of malignancy in several cancer types including lung. In the present study, we defined the role of PTTG in actin cytoskeleton remodeling, cell migration and induction of epithelial mesenchymal transition (EMT) through the regulation of integrin α(V)β(3)-FAK signaling pathway. Overexpression of PTTG through an adenovirus vector resulted in a significant increase in the expression of integrins α(V) and β(3), a process that was reversed with the down-regulation of PTTG expression through the use of an adenovirus expressing PTTG-specific siRNA. Western blot analysis of cells infected with adenovirus PTTG cDNA resulted in increased FAK and enhanced expression of adhesion complex molecules paxillin, metavincullin, and talin. Furthermore, downstream signaling genes Rac1, RhoA, Cdc42, and DOCK180 showed up-regulation upon PTTG overexpression. This process was dependent on integrin α(V) as blockage by antagonist echistatin (RGD peptide) or α(V)-specific siRNA resulted in a decrease in FAK and subsequent adhesion molecules. Actin cytoskeleton disruption was detected as a result of integrin-FAK signaling by PTTG as well as enhanced cell motility. Taken together our results suggest for the first time an important role of PTTG in regulation of integrins α(V) and β(3) and adhesion complex proteins leading to induction of EMT.